Ovarian high-grade serous carcinoma with estrogenic manifestations in a postmenopausal woman: A case report - Akihiro Takeda; Kazuko Watanabe (Elsevier, 2023)
Background: Hormonally active ovarian tumors include a variety of pathologies such as sex-cord-stromal tumors, germ cell tumors, tumors with neuroendocrine differentiation, and tumors with functioning stroma. In addition, although the precise mechanism is unknown, epithelial ovarian cancers can be associated with elevated serum estrogen levels on rare occasions. Case: A 56-year-old postmenopausal woman (gravida 3, para 3) with a history of hyperlipidemia was referred due to the discovery of a heterogenous right adnexal mass after presenting to her physician with genital bleeding and nipple discharge associated with breast tension. Her serum cancer antigen 125 (CA125) level was 136.5 U/mL at the initial examination, and serum estradiol and testosterone levels were 214.8 pg/mL and 236.3 ng/dL, respectively. Endometrial thickening was also observed. The diagnosis was a mixed cystic and solid right adnexal mass, implying malignant ovarian tumor but not completely ruling out sex-cord-stromal tumor. Laparoscopic-assisted vaginal hysterectomy, bilateral salpingo-oophorectomy, and partial omentectomy were performed. Cancer cells were detected in the peritoneal cytology of pooled ascites. Histological examination revealed high-grade serous carcinoma of the right ovary. Six cycles of paclitaxel and carboplatin chemotherapy were administered postoperatively. At three-year follow-up, there was no evidence of disease recurrence, including re-elevation of CA125, or of serum estradiol, or of testosterone. Conclusions: Epithelial ovarian cancer should be considered in postmenopausal women presenting with a pelvic mass and raised hormonal profile, and these patients should be managed according to an epithelial ovarian cancer treatment paradigm.